ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA BOS PADA SDS ADVENT 6 MEDAN - Simamora, Amoy Dameria; Maisyarah, Renny; Tripriyono, Agus (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The purpose of this research is to delve into the practices related to the implementation of accountability and transparency principles in the management of school operational assistance (BOS). The independent variables used in this study include key aspects of accountability, including financial reporting, fund utilization, school accountability in managing BOS funds, as well as transparency, which includes the extent to which information is open to parents or school supervisory bodies, and school characteristics. Meanwhile, the two dependent variables considered are the efficiency of BOS fund utilization and the school's ability to comply with guidelines and regulations in the management of BOS funds. This research uses a qualitative descriptive analysis approach, relying on qualitative data obtained from interviews and financial report analysis. The data used in this study are secondary in nature, including information from various sources related to the management of BOS funds in various schools. Through this approach, the research aims to delve deeper into the practices related to accountability and transparency in the management of BOS funds, and to provide a more comprehensive understanding of how these principles are applied in practical contexts.